RELATIONSHIPS BETWEEN CONFLICT BEHAVIOR AND CONFLICT SITUATIONS IN THE STUDENT COMMUNITY - Berdieva Gulmira Jurayevna (Journals Park Publishing, 2022)
This article discusses the relationship between conflict behavior and conflict situations in the student community. Based on pedagogical data and written sources, the author clarified the problem on the basis of available scientific literature and studied the existing specific aspects of the relationship between conflict behavior and conflict situations in the student community.
Keywords: Students, conflict behavior, situations, psychology.